Long-acting β2-adrenoreceptor agonists suppress type 1 interferon expression in human plasmacytoid dendritic cells via epigenetic regulation. (February 2018) - Kuo, Chang-Hung; Yang, San-Nan; Tsai, Yi-Giien; Hsieh, Chong-Chao; Liao, Wei-Ting; Chen, Li-Chen; Lee, Min-Sheng; Kuo, Hsuan-Fu; Lin, Ching-Hsiung; Hung, Chih-Hsing
Abstract: The combination of inhaled long-acting β2-adrenoreceptor (LABA) and inhaled glucocorticoid (ICS) is a major therapy for asthma. However, the increased risk of infection is still a concern. Plasmacytoid dendritic cells (pDCs) are the predominant cells producing type 1 interferon (IFN) against infection. The effect of LABA/ICS on type 1 IFN expression in human pDCs is unknown. Circulating pDCs were isolated from healthy human subjects and were pretreated with glucocorticoid (GCS), LABA or a cAMP analog, and were stimulated with Toll-like receptor (TLR) agonist CpG (TLR9) or imiquimod (TLR7) in the presence of IL-3. The expression of type 1 IFN (IFN-α/β) were measured by ELISA. The mechanisms were investigated using receptor antagonists, pathway inhibitors, Western blotting and chromatin immunoprecipitation. GCS suppressed TLR-induced IFN-α expression, and LABA enhanced the suppressive effect. LABA alone also suppressed TLR-induced IFN-α/β expression, and the effect was reversed by the β2-adrenoreceptor antagonist ICI118551. Dibutyryl-cAMP, a cAMP analog, conferred a similar suppressive effect, and the effect was abrogated by the exchange protein directly activated by cAMP (Epac) inhibitor HJC0197 or intracellular free Ca 2+ chelator BAPTA-AM. Formoterol suppressed TLR-induced phosphorylation of mitogen-activated protein kinase (MAPK)-p38/ERK. Formoterol suppressed interferon regulatory factor (IRF)-3/IRF-7 expression. Formoterol suppressed CpG-induced translocation of H3K4 specific methyltransferase WDR5 and suppressed H3K4 trimethylation in the IFNA and IFNB gene promoter region. LABA suppressed TLR7/9-induced type 1 IFNs production, at least partly, via the β2 -adrenoreceptor-cAMP-Epac-Ca 2+, IRF-3/IRF-7, the MAPK-p38/ERK pathway, and epigenetic regulation by suppressing histone H3K4 trimethylation through inhibiting the translocation of WDR5 from cytoplasm to nucleus. LABA may interfere with anti-viral immunity.